Crambescin C1 Acts as A Possible Substrate of iNOS and eNOS Increasing Nitric Oxide Production and Inducing In Vivo Hypotensive Effect - Rubiolo, Juan A.; Lence, Emilio; González-Bello, Concepción; Roel, María; Gil-Longo, José; Campos-Toimil, Manuel; Ternon, Eva; Thomas, Olivier P.; González-Cantalapiedra, Antonio; López-Alonso, Henar; Vieytes, Mercedes R.; Botana, Luis M. (Frontiers in Pharmacology, 2021)
Crambescins are guanidine alkaloids from the sponge Crambe crambe. Crambescine C induces metallothionein genes and nitric oxide is one of the triggers. We studied and compared in silico, in vitro and, in vivo the effect of the analogs crambescine A, C, and homo C. HepG2 gene expression was analyzed using microarrays and additional assays used isolated rat aortic rings. The targets of crambescines were studied in silico. In vivo vasodilation in rats was done by direct measurement. Crambescines C and homo-crambescine C, but not crambescine A, induced metallothioneins transcripts. HepG2 cells with crambescine C increased nitric oxide production. Vasodilation was observed in aortic ring and in vivo after injection in rats. In silico analysis points to eNOS and iNOS as targets of crambescin C and source of nitric oxide increment. Crambescin C effect is mediated through crambescing binding to the active site of eNOS and iNOS. In isolated rat aortic rings CC and HCC induced an endothelium-dependent relaxation related to eNOS activation and an endothelium-independent relaxation related to iNOS activation, hence both compounds increase NO and reduce vascular tone. Crambescin C1 docking studies in iNOS and eNOS active site revealed hydrogen bonding of the hydroxylated chain with residues Glu377 and Glu361, involved in the substrate recognition, and explains its higher binding affinity than Crambescin A1. The later interaction and the extra polar contacts with its pyrimidine moiety, absent in the endogenous substrate, explain its role as exogenous substrate of NOSs and NO production.